Large Scale Processes for Understanding Extreme Rain Storm Over Rangamati on 12 June 2017- A Case Study (Journal of Engineering Science, 2020)
Attempts have been made to study the large-scale surface and upper air synoptic processes associated with a monsoon depression during 11-12 June 2017. In this study, Grid Analysis and Display System (GrADS) software has been used to prepare the large-scale sea level pressure and upper flow patterns by analyzing the FNL re-analysis data. In this analysis, FNL dataset is used to characterize the rainstorms, with key hydrometeorological variables describing the prior conditions of the very heavy rainfall event presented the study. National Center for Environmental Prediction (NCEP) Final (FNL) analysis data of 1o by 1o grids for every 6 hours are used for large scale synoptic analysis. The disastrous event was a strong monsoon depression in the early period of southwest monsoon 2017. Due to this depression, very heavy rainfall occurred in the southeastern Bangladesh. Rangamati recorded 343 mm of rainfall in the 24 hours on 12 June 2017. Massive landslides occurred in three districts such as Rangamati, Bandarban and Chittagong. The analysis of surface and upper air synoptic conditions has revealed that a well-marked low was formed over the northwest Bay of Bengal within the low-pressure belt passing from Somalia coast extending through southern Pakistan, and India up to east central Bay of Bengal and adjoining Bangladesh. The wind speed is calculated from the pressure distribution and is found to be 24.23ms-1, which is at par with the observed one. The well-marked low was subsequently intensified into a depression and moved northeastwards over Bangladesh. Strong southsouthwesterly winds were associated in the eastern side of the depression, especially over Chittagong Hill Tracts. The depression was found to extend up to 500 hPa level as seen from the distribution of geopotential and strong circulation around the centre. Winds were advecting from large continental and Ocean areas over the South Asia. Strong winds and moisture influx, strong narrow coma-like trough from a micro low at the surface to 500 hPa level as well as strong wind shear were responsible for the heavy rainfall, disastrous effects and massive landslides over Rangamati and adjoining areas.Journal of Engineering Science 11(2), 2020, 87-97